Identification of Disaster Evacuation Routes in the Faculty of Education Building at Universitas Negeri Medan - Nainggolan, Edoy; Ilvaldo, Iqbal; Sembiring, Lin Arsenna Br; Pratama, Alvin; Arbiansyah, Arbiansyah; Sianturi, Stevan Federico (Jurnal Penelitian Geografi (JPG), 2024)
Disaster evacuation management in the Faculty of Education building, State University of Medan is very crucial because it involves high risks for its occupants. As a place for learning activities and large events, safety and smooth evacuation during disasters such as fires or earthquakes must be prioritized. This study aims to describe an efficient evacuation route in the Faculty of Education building, State University of Medan. The research method used is qualitative with a descriptive approach. Data were collected through interviews, observations, and field surveys to obtain an overview of the condition of the Faculty of Education (FIP) building and its surroundings. The results of the study indicate that the Faculty of Education building, State University of Medan does not fully meet the evacuation route standards stipulated in the applicable disaster regulations. The evacuation route includes stairs, exits, and alternative routes that must be usable in various disaster scenarios. This study also found several areas in the building that needed improvement related to evacuation safety and accessibility. These findings can be the basis for improving and enhancing the disaster plan in the Faculty of Education Building as well as a guide for related parties to optimize evacuation routes, increase awareness of disasters, and strengthen the capacity to respond to natural and non-natural disasters in the university environment. Keywords: evacuation;croute; disaster; earthquake